Best Answer

3j-13=11+2j

3j-13-2j = 11+2j-2

j-13 = 11

j-13 +13 = 11 + 13 = 24

so j = 24

Q: How do you solve 3j - 13 equals 11 plus 2j?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

-2x+13y=11 13y=2x+11 y=2x/13 + 11/13

13=e+2 11=e (subtract 2 from each side)

5

X +13 equals 22, X equals nine

12 + 5 equals...

-11

-13 + 24 = 11

4r + 13 = 57subtract 13 from both sides:4r + 13 - 13 = 57 -134r = 44divide both sides by 4 to solve for r:4r/4 = 44/4r = 11

To solve for x, we'd have to know what this expression equals.

basically you asked what -28+21 which equals -7

13=m+2m=11

If: 2a+13 = 5a+1 Then: a = 4